The relationship between exposure to particulate matter and breast cancer incidence and mortality: A meta-analysis - Zhang, Zhe (Medicine (Baltimore), 2019)
BACKGROUND: Particulate matter (PM) acts as an environment pollutant and thus plays a vital role in the development of human lung cancer. Whether PM is a risk factor for breast cancer (BC) morbidity and mortality, however, is not clear. Recently, several studies have reported inconsistent results for the association between PM and BC risk. This meta-analysis examines the indefinite relationship between exposure to PM and BC morbidity and mortality. METHODS: Based on a search of Pubmed, Embase, Web of Science and Cochrane Library, the hazard ratio (HR) and 95% confidence interval (CI) were extracted and analyzed by Review Manager 5.3 and Stata14.0 to estimate the association between PM and BC morbidity and mortality. The heterogeneity for the included studies was evaluated using a Chi-square test and the I(2) statistic. Forest plot was used to illustrate the pooled HR and mean difference. A Funnel plot, Begg test, and Egger test were performed to explore the publication bias between the included studies. All analyses were based on previous published studies, thus, no ethical approval and patient consent are required. RESULTS: A total of 14 of 284 publications with 1,004,128 BC cases were gathered. The analysis showed each 10 μg/m(3) of PM(2.5) (diameter ≤2.5 μm) was associated with 1.17 (95% CI: 1.05–1.30, P = .004) fold risk BC mortality, and each 10 μg/m(3) of PM(10) (diameter ≤10 μm) was associated with 1.11 (95% CI: 1.02–1.21, P = .021) fold risk BC mortality. However, neither PM(10) nor PM(2.5) was found to be significantly associated with BC morbidity. Publication bias was detected in studies on PM(2.5) and BC mortality. CONCLUSIONS: Our study suggests that PM exposure may raise the mortality but not the morbidity of BC. Still, further studies may be necessary to confirm this finding.